Study on the characterization of differential weathering feature based on surface roughness theory and 3D laser scanning: A case study of the Suoyang Ancient City. - Guo, Zhiqian; Qi, Qiang; Zhang, Shuai; Chen, Wenwu; Wu, Chong; Wu, Haiyu (Journal of Cultural Heritage, 2023)
• The morphology of differential weathering is digitized by 3D laser scanning. • The differential weathering features are characterized by the roughness indexes. • How spatial features of walls affect the differential weathering is discussed. • The classification of differential weathering degree is explored preliminarily. Earthen heritage sites have been undergoing lengthy surface weathering since they were built, which can pose a severe threat to the protection and utilization of these cultural treasures. Especially for differential weathering, one of the most common surface weathering patterns of earthen heritage sites in northwestern China, has not been well studied yet. Hence, in this paper, Suoyang Ancient City was selected as the study area, and six analysis domains (S1 to S6) exhibiting various differential weathering degrees were determined on wall faces and their morphological data were collected by a 3D laser scanner. Based on the point cloud data, the morphology of each domain was digitalized and reconstructed, and ten typical profiles were selected for roughness analysis. Concretely, for these profiles, six roughness parameters, including average asperity inclination (A i), mean curvature (R′da), textural slope parameter (Z 2), roughness coefficient (R p), self-affine fractal dimensions (A and D) and directional roughness metric (G (i)) were calculated to characterize their differential weathering features. The results show that the wall with a higher differential weathering degree has greater values of R p , G (i), A and D. It can also be found that different roughness indicators can reflect different wall surface morphological characteristics. In addition, the main driver of differential weathering developing is the prevailing sediment-laden wind, and the degree of differential weathering is also affected by the building techniques, wall endowment environment, wall orientation and morphology. Finally, according to the roughness values and wall surface morphology, the differential weathering degrees were classified into five grades (from level I to level V). In this case, the differential weathering degrees of S2 (level IV) and S5 (level IV) are the highest, followed by S3 (level III), S6 (level III), S1 (level II) and S4 (level II) respectively. Overall, the proposed approach based on 3D scanning and surface roughness is feasible to characterize the differential weathering degree, contributing to better prevention and mitigation of damage on earthen heritage sites.